Manifestations of the Epidemic Process of Community-Acquired Pneumonia among HIV-Infected Patients and Dependence of Incidence of Infection on the Level of Immunodeficiency and Viral Load - V. I. Sergevnin; К. V. Ovchinnikov (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. One of the most common opportunistic infections among HIV-infected people is community-acquired pneumonia (CAP).Aim. To determine the features of the epidemic process of CAP in HIV-infected patients and to study the incidence of infection depending on the level of immunodeficiency and viral load.Materials and methods. The epidemiological manifestations of the incidence of CAP among HIV-positive and HIV-negative population of Perm Region in 2014–2019 were studied. The incidence of CAP in HIV-infected patients was determined in dependence on the level of immunodeficiency (230 patients) and viral load (132 patients). Results. The incidence of CAP among HIV-infected in some years exceeds the incidence of HIV-negative residents in 3.9–9.3 times. Other manifestations of the epidemic process of CAP among HIV-positive and HIV-negative patients are similar. The risk group for CAP morbidity among HIV-positive and HIV-negative people are children in their earliest years and people over the age of 60. Urban residents and men become ill more frequently. The subannual dynamics of the epidemic process is characterized by moderate seasonality during the cold period of the year. CAP is most often recorded when CD4 + lymphocytes are less than 200 cells/μl and viral load of 10,000–100,000 copies/ml.Conclusion. HIV-infected people are at risk group of CAP morbidity. The incidence of CAP in HIV-infected people expands with an increase in immunodeficiency and viral load.